The incidence of surgical site infection and its predictors among women delivered via cesarean sections in Ethiopia: a systematic review and meta-analysis - Wondmeneh, Temesgen Gebeyehu; Mohammed, Jemal Abdu (Frontiers in Medicine, 2024)
Background: Although surgical wound infection remains a serious issue worldwide, the disease burden is greater in developing countries, including Ethiopia. Even though there were primary studies conducted at district levels in Ethiopia, there is little evidence about the pooled incidence of surgical site infections at the national level. Thus, this systematic review and meta-analysis determined the pooled incidence of surgical site infection and its associated factors among caesarean-delivered women in Ethiopia.We searched PubMed, CINAHL, African Journals Online, Google Scholar, and higher educational institutional repositories. A random-effects model was used to estimate the pooled effect size with 95% confidence intervals (CIs). Funnel plot and egger tests were computed to determine the existence of publication bias. A subgroup analysis was carried out.Twenty-three studies were included in the final analysis. The pooled incidence of surgical site infection among women delivered via cesarean section was 12.32% (95% CI: 8.96-16.11%). Rural residence (AOR = 2.51, 95% CI: 1.15-3.87), membrane rupture (AOR = 2.04, 95% CI: 1.24-2.85), chorioammionitis (AOR = 4.13, 95% CI:1.45-6.8), general anesthesia (AOR = 1.99, 95% CI: 1.22-2.75), post-operative Hgb level less than 11 mg/dl (AOR = 3.25, 95% CI: 1.54-4.96) and membrane rupture greater or equal to 12 hours (AOR = 3.93, 95% CI: 1.93-5.92) were independent risk factors for surgical site infections.More than one in ten women delivered via cesarean section developed surgical site infections in Ethiopia. Women living in rural areas and those with a membrane rupture, chorioammionitis, or anemia should be given special attention.General anesthesia should not be a mandatory procedure.